(untitled) (Washington, D.C., 1986)
This volume provides a state-of-the-art review of the relationship between technology and economic growth. Many of the 42 chapters discuss the political and corporate decisions for what one author calls a "Competitiveness Policy." As contributor John A. Young states, "Technology is our strongest advantage in world competition. Yet we do not capitalize on our preeminent position, and other countries are rapidly closing the gap." This lively volume provides many fresh insights including "two unusually balanced and illuminating discussions of Japan.
Keywords: Đổi mới công nghệ,Technological innovations; Hội nghị,Congresses; Hoa Kỳ,United States